Exploring EFL Learners’ and Teachers’ perspectives in an International Online Exchange Program - Sifreni Mira Yusiana; Rizal Wahid Permana; Sonny Elfiyanto; Junaidi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
In today’s interconnected world, fostering intercultural understanding and language acquisition among young learners is increasingly vital. Online exchange programs have emerged as accessible alternatives to traditional exchanges, enabling students to interact globally and build intercultural competencies. This qualitative case study explores the perspectives of English as a Foreign Language (EFL) teachers and students engaged in an intensive international online exchange program organized by With The World Incorporation, Japan. The study aimed to identify challenges faced by participants and the strategies employed to overcome them, offering a holistic understanding of the online exchange experience. Data were collected through interviews, observations, and document analysis, involving one teacher, a program coordinator, and actively participating students. Thematic analysis revealed challenges such as technical and connectivity issues, language proficiency barriers, sustaining engagement, scheduling conflicts, and cultural differences. Despite these obstacles, the program proved effective through proactive planning, strong technical and logistical support, psychologically safe and task-based pedagogy, engaging content, and continuous feedback. These findings align with established theories, including the digital divide, foreign language anxiety, and self-determination theory. The study highlights how adaptive strategies can transform barriers into opportunities to enhance English proficiency, promote intercultural understanding, and develop global competencies. The results provide practical implications for educators and program designers, emphasizing dynamic content, adaptive teaching approaches, and feedback mechanisms to optimize future online exchange initiatives.